Ivy Anning interviewed by Ainslie Evans for the Australia 1938 oral history project - Anning, Ivy, 1919-; Evans, Ainslie; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Anning speaks of her family background; school and childhood memories; family life; employment experiences and conditions; death of father; courtship and marriage; children and childcare; family lifestyle; recreation; attitudes to Aborigines and migrants; Australian society; the Depression; family experiences after the 1940's; religion; social life; entertainment.
Recording is accompanied by photographs.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Full transcript unavailable, partially transcribed (3 p.)
Keywords: Anning, Ivy, -- 1919- -- Interviews; Albany (W.A.) -- Social conditions